Internationalization of business research: New locations gaining ground - Heike Belitz (DIW Economic Bulletin, 2012)
In recent years, German and foreign companies have consistently increased their investment in Research and Development in Germany. In 2009, investment was over 45 billion euros which was a third higher than in 2001. While foreign companies have significantly expanded their Research and Development activities in Germany, German investment abroad has stagnated. Overall, Germany had a positive balance of four billion euros. There is no evidence of large-scale relocation of German Research and Development abroad. German companies' foreign research activities continue to be conducted predominantly in the US, and in neighboring European countries, but also increasingly in certain Central and East European countries as well as in China and South-East Asia. Nowadays, approximately one in ten inventions developed by German companies abroad originate at one of the new research sites although German companies are by no means more active than their competitors in these new research locations.
Keywords: F23; O3; O57; 330; globalization; MNCs; research and development; patents